Metagenomic sequencing for identification of nontuberculous mycobacteria and other pathogens in patients with mixed infection of the lung - Yu, Jinyan; Lv, Xuejiao; Wang, Qi; Gao, Mingyue; Li, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundIt can be difficult to distinguish lung disease caused by nontuberculous mycobacteria (NTM), Mycobacterium tuberculosis, and mixed infections (MIs) that include NTM. Metagenomic next generation sequencing (mNGS) is a highly sensitive method that can reliably identify lung pathogens. We retrospectively analyzed the records of patients who had MIs of the lungs that included NTM and received mNGS testing.MethodsThe records of 36 patients who were diagnosed with NTM infection of the lungs at the Second Hospital of Jilin University from Nov 2023 to Jun 2024 were analyzed. Initial empirical treatments were ineffective in all patients, leading to the application of mNGS of bronchoalveolar lavage fluid (BALF).ResultsThe average patient age was 62.4 years, 22 patients had one or more underlying chronic disease, and all patients had at least one respiratory symptom (cough, sputum production, fever, or dyspnea). Chest CT examinations showed that patients had different degrees of pneumonia and pleural effusion. Among tested patients, there were elevated levels of erythrocyte sedimentation rate in 81.8% (18/22) and elevated C-reactive protein in 90.5% (19/21). There were variable results from acid-fast staining of bronchoalveolar lavage fluid (BALF; 3/36, 8.3%), and transbronchial lung biopsy (TBLB; 5/14, 35.7%). mNGS identified seven NTM species. Treatment based on the mNGS results led to the resolution of clinical symptoms and absorption of lung lesions in all patients.ConclusionsMost of the 36 patients with MIs of the lungs that included NTM had underlying diseases. The results of traditional tests, including sputum or BALF culture and smear, acute phase markers, and TBLB pathological examination, were problematic. mNGS provides rapid and reliable diagnosis, allowing the rapid implementation of appropriate therapy in patients with MIs of the lungs that include NTM.